2019
DOI: 10.1002/mgg3.625
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of the phenotypic spectrum and description of molecular findings in a cohort of patients with oculocutaneous mosaic RASopathies

Abstract: Background Postzygotic KRAS , HRAS , NRAS , and FGFR1 mutations result in a group of mosaic RASopathies characterized by related developmental anomalies in eye, skin, heart, and brain. These oculocutaneous disorders include oculoectodermal syndrome (OES) encephalo‐cranio‐cutaneous lipomatosis (ECCL), and Schimmelpenning‐Feuerstein‐Mims syndrome (SFMS). Here, we report the results of the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 74 publications
4
30
0
Order By: Relevance
“…Recent genetic studies have demonstrated mosaic mutations in FGFR1, KRAS and NRAS genes as well as constitutive activation of RAS-MAPK signaling pathway in patients with ECCL. [5][6][7] These findings support earlier hypotheses that ECCL results from a post-zygotic, sporadic, lethal mutation affecting mesenchymal derivatives and surviving due to somatic mosaicism. 2,8 The cutaneous hallmark of ECCL is nevus psiloliparis (NP), a hairless fatty nevus that was seen in 44 out of 54 cases reviewed by Moog.…”
Section: Discussionsupporting
confidence: 87%
“…Recent genetic studies have demonstrated mosaic mutations in FGFR1, KRAS and NRAS genes as well as constitutive activation of RAS-MAPK signaling pathway in patients with ECCL. [5][6][7] These findings support earlier hypotheses that ECCL results from a post-zygotic, sporadic, lethal mutation affecting mesenchymal derivatives and surviving due to somatic mosaicism. 2,8 The cutaneous hallmark of ECCL is nevus psiloliparis (NP), a hairless fatty nevus that was seen in 44 out of 54 cases reviewed by Moog.…”
Section: Discussionsupporting
confidence: 87%
“…those with a 5% Minor Allele Frequency (MAF) in at least one populational frequency database such as the 1,000 Genomes Project (Lek et al, 2016), 6,500 NHLBI GO Exome Sequencing Project (Tennessen et al, 2012), Exome Aggregation Consortium (Lek et al, 2016), TOPMed (NHLBI Trans-Omics for Precision Medicine WGS-About TOPMed) and ABraOM (Naslavsky et al, 2017) databases. The variants in mature miRNAs associated with known phenotypes of RASopathies as well as cardio-cerebrovascular diseases (Calcagni et al, 2017; Chacon-Camacho et al, 2019); (Cao et al, 2017) and cancer diseases (Hernández-Martín and Torrelo, 2011; Villani et al, 2017; Keshari et al, 2018; Rauen et al, 2018) were also selected. All known predicted and validated target genes from the polymorphic miRNA list were retrieved from the DIANA tools online suite (Vlachos and Hatzigeorgiou, 2017) and miRTARBASE with the SpiderMiR package (Cava et al, 2017) in R. The resulting list of target genes was used as a query for over-representation analysis with the KEGG and Gene Ontology (GO) databases using the clusterProfiler package (Yu, 2018) in R. Over-representation analysis of rare diseases according to the NIH (National Institutes of Health) and GARD (Genetic and Rare Disesases Information Center) was performed using the ARCHS4 predictions of GeneRIF with the Enrichr web tool (Kuleshov et al, 2016; Lachmann et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…RAS isoforms play a crucial role in regulating cell survival, proliferation and differentiation [ 7 9 ]. Germline mutations in RAS and other members of the MAPK pathway (e.g., KRAS , HRAS and NRAS ) may cause rare inherited disorders known as “RASopathies”, including LNSS and nevus sebaceous [ 7 , 10 ]. In a study that included 2 LNSS patients and 63 patients with nevus sebaceous, Groesser et al identified HRAS mutations (mostly c.37G > C) in 95% of the cases, and KRAS mutations in the remaining 5% of the cases [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…A shared somatic mosaic KRAS mutation (c.35G > A) has been reported in the cutaneous lesions of 4 cases of LNSS [ 2 , 11 13 ]. A recent study proposed that the mutation could account for most cases of LNSS [ 10 ].…”
Section: Discussionmentioning
confidence: 99%